Mapping the Evolution of Six Sigma in Quality Management: A Bibliometric Review (2000–2025) - Judijanto, Loso; Ummah, Andrian Khoirul (The Eastasouth Management and Business, 2025)
This study conducts a bibliometric review to map the evolution of Six Sigma in the field of quality management from 2000 to 2025. Using the Scopus database as the primary source and analyzed through VOSviewer, the study explores publication trends, keyword co-occurrence, and collaboration networks to uncover the intellectual structure and thematic progression of Six Sigma research. The findings highlight the central role of Six Sigma and Total Quality Management (TQM) as dominant research themes, while emerging areas such as Lean Six Sigma, healthcare quality, process improvement, and risk management illustrate the method’s expansion into diverse industries and organizational functions. The density and overlay visualizations further reveal a shift from traditional manufacturing-based applications toward service sectors, healthcare systems, and strategic management contexts, demonstrating the adaptability and resilience of Six Sigma in addressing contemporary challenges. This review contributes to the literature by offering both a theoretical mapping of research trajectories and practical implications for organizations aiming to leverage Six Sigma for sustainable quality improvement and innovation.